MODIFICATION AND REINFORCEMENT OF INTUMESCENT EPOXY COATINGS - ШОЛОГОН, В. І.; ВАХІТОВ, Р. А.; КАЛАФАТ, К. В.; ТАРАН, Н. А.; БЕССАРАБОВ, В. І.; ВАХІТОВА, Л. М. (Technologies and Engineering, 2023)
Purpose. To investigate the effect of nanosubstances, reinforcing fibres, inorganic fire retardants and their mixtures on the formation of a protective char layer and the fire retardant efficiency of epoxy coatings of the formulation ammonium polyphosphate/melamine/pentaerythritol/titanium dioxide/epoxy resin. Methodology. A fire retardant polyphosphate mixture containing an epoxy resin of bisphenols A/F together with a polyamidoamine hardener was chosen as a model intumescent system. The effect of fire retardants and reinforcing additives on the temperature decomposition of the intumescent coating was determined by thermogravimetry. The intumescent coefficient and the weight of the char residue of the intumescent compositions were studied in stages in the temperature range of 200–800 °C. Fire tests were performed in a mini-oven under standard fire conditions according to the method. Findings. The effect of nanographite, nanoclay, mineral fibre, and inorganic fire retardants on the formation and physical characteristics of the char layer of the ammonium polyphosphate/melamine/ pentaerythritol/epoxy resin intumescent system in the temperature range of 200–800 °C was studied. It was found that the fire protection efficiency of the coating decreases in the following order: graphite oxynitrate/organomodified montmorillonite > organomodified montmorillonite > zinc borate > graphite oxynitrate/mineral fibre. The formulation of an intumescent system based on epoxy resin with fire retardant and reinforcing additives (organomodified montmorillonite, graphite oxynitrate, zinc borate and mineral fibre) was developed, the effectiveness of which was proved by fire tests. Scientific novelty. The influence of graphite oxynitrate and its mixtures with nanosubstances and fire retardants on the formation of the char layer and the fire protection efficiency of the epoxy intumescent coating was studied for the first time. Practical significance. The optimum composition of nanosubstances, reinforcing fibre and inorganic fire retardants for the design of intumescent epoxy coatings with enhanced fire protection properties has been established.